An Intrinsic MicroRNA Timer Regulates Progressive Decline in Shoot Regenerative Capacity in Plants. Issue 2 (3rd February 2015) - Zhang, Tian-Qi; Lian, Heng; Tang, Hongbo; Dolezal, Karel; Zhou, Chuan-Miao; Yu, Sha; Chen, Juan-Hua; Chen, Qi; Liu, Hongtao; Ljung, Karin; Wang, Jia-Wei
Abstract : Age regulates plant regenerative capacity. Abstract: Plant cells are totipotent and competent to regenerate from differentiated organs. It has been shown that two phytohormones, auxin and cytokinin, play critical roles within this process. As in animals, the regenerative capacity declines with age in plants, but the molecular basis for this phenomenon remains elusive. Here, we demonstrate that an age-regulated microRNA, miR156, regulates shoot regenerative capacity. As a plant ages, the gradual increase in miR156-targeted SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPL) transcription factors leads to the progressive decline in shoot regenerative capacity. In old plants, SPL reduces shoot regenerative capacity by attenuating the cytokinin response through binding with the B-type ARABIDOPSIS RESPONSE REGULATORs, which encode the transcriptional activators in the cytokinin signaling pathway. Consistently, the increased amount of exogenous cytokinin complements the reduced shoot regenerative capacity in old plants. Therefore, the recruitment of age cues in response to cytokinin contributes to shoot regenerative competence.